Spectrum sensing in cognitive vehicular networks for uniform mobility model. Issue 19 (1st December 2019) - Paul, Anal; Kunarapu, Priyatham; Banerjee, Avik; Maity, Santi P.
Abstract : Cooperation among the sensing nodes in cognitive radio (CR) networks improves spectrum sensing (SS) reliability. However, determining the efficient set of secondary users (SUs) to be involved in cooperative SS (CSS) becomes challenging in vehicular networks (VNs) due to the mobility of primary user (PU) and/or SU nodes. This work explores an energy detection‐based CSS scheme in CR enabled VNs (CR‐VNs) considering the uniform velocity motion of PU and SU nodes. A distance‐dependent distribution function is developed first to find the probability of a SU resides in a specific coverage of the PU transmission zone. This distribution function is then used in deriving the expression of the probability of detection and probability of false alarm using majority rule at the fusion centre. The efficacy of the mathematical analysis is studied through a large set of simulation results that highlight the enhanced SS performance in terms of the probability of detection by ∼ 2.11, and ∼ 6.56 % at uniform velocity over the existing works in CR‐VN.